2015
DOI: 10.15608/stjssa.v11i2.225
|View full text |Cite
|
Sign up to set email alerts
|

Runoff, Erosion and Nutrient Sediment due The Vegetative Soil Conservation on Oil Palm Plantation

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
0
3
0
1
Order By: Relevance
“…Dariah et al (2002) say that stems, twigs, and leaves will cover the surface of the soil and reduce the strength of rainwater eroding the soil. Added by Fuady et al(2014) that planting M. bracteata can also reduce the volume of surface run off and increase soil infiltration. This is because the cover crop of M. bracteata has a fast growing power that can cover the surface of the soil so that the rainwater does not fall directly to the ground surface.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dariah et al (2002) say that stems, twigs, and leaves will cover the surface of the soil and reduce the strength of rainwater eroding the soil. Added by Fuady et al(2014) that planting M. bracteata can also reduce the volume of surface run off and increase soil infiltration. This is because the cover crop of M. bracteata has a fast growing power that can cover the surface of the soil so that the rainwater does not fall directly to the ground surface.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to chemical soil cover also affects soil physics. Fuady et al (2014) stated that vegetation conservation techniques (ground cover) can suppress surface runoff, soil erosion, and nutrient loss. According to (Nusyirwan, 2014) the benefits of using ground cover include reducing erosion, adding organic material, improving soil structure, accelerating infiltration and increasing nitrogen.…”
Section: Introductionmentioning
confidence: 99%
“…It showed that nutrients are present on A2 and provide a positive response to weight of fresh plants. Availability of nutrients that can absorbed by plants is one possible factor influences level production and growth of plants, so if the required nutrients for growth are fulfilled, plants will obtain optimal production as well quality [22]. Precise concentrations could supports metabolic processes in plants and have a good influence on growth and production [23].…”
Section: Plant Fresh Weightmentioning
confidence: 99%
“…Lereng atau kemiringan lahan adalah salah satu faktor pemicu terjadinya erosi dan longsor di lahan pegunungan. Erosi membawa lapisan tanah permukaan yang umumnya lebih subur, kaya bahan organik dan unsur hara sehingga menyebabkan hilangnya unsur hara bagi tanaman (Fuady et al, 2014). Hal tersebut sesuai dengan data yang diperoleh yaitu tinggi batang kelapa sawit pada lahan miring tumbuh paling pendek dan batang sawit tertinggi ditunjukkan sawit dilahan datar.…”
Section: Tinggi Batang Sawitunclassified